The Importance of Metacognitive Listening Strategy in English Listening Improvement: A Review - Alber, Alber; Safriyanti, Maria (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
The metacognitive listening strategy has an important role in the process of enhancing English listening comprehension. This article reviewed six empirical studies related to the impact of metacognitive listening strategy use while learners tried to improve their listening comprehension in different environments. The findings showed that learners used some metacognitive listening strategies to help them to comprehend the listening text tasks. It also indicated that various factors affect learners’ successful learning on their listening comprehension improvement. It can be concluded that the metacognitive listening strategy has had a positive impact while they are used regularly in the language learning process.